Persepsi Literasi Halal dan Motif Pemilihan Produk Kosmetik Mahasiswa Universitas KH. A. Wahab Hasbullah - Amin Awal Amarudin; Adinda Syaifa Azzara; Efnita Mayang Sari; Haya Fatimah; Lailatul Afifah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research has a relationship between perceptions of halal literacy and UNWAHA students' motives for choosing cosmetic products based on sharia economic principles. Through an economic analysis approach, this research explores the extent to which students' understanding of halal literacy influences their motives for choosing halal cosmetic products that follow sharia principles. This research method uses a qualitative approach with data sources through interviews with UNWAHA students. It is hoped that the research results will provide valuable insight for students in understanding halal literacy and motives for choosing cosmetic products.